INA-CBGs claim versus total hospital cost: A vaginal delivery investigation at Airlangga University Academic Hospital, Indonesia - Manggala Pasca Wardhana; Khanisyah Erza Gumilar; Prima Rahmadhany; Erni Rosita Dewi; Muhammad Ardian Cahya Laksana (SAGE Publishing, 2020)
Background: Inadequate funding for vaginal delivery can be one of the barriers to reducing the maternal mortality rate. It could be therefore critical to compare the vaginal delivery cost between total hospital cost and INA-CBGs cost in national health insurance.  Methods: This was a retrospective cross-sectional study conducted from October to December 2019 in Universitas Airlangga Academic Hospital. It collected data on primary diagnosis, length of stay, total hospital cost, INA-CBGs cost, and counted disparity. The data analyzed statistically using t-test independent sample (or Mann-Whitney test). Results: A total of 149 vaginal delivery claims were found, with the majority having a level II severity (79.87%) and moderate preeclampsia as a primary diagnosis (20.1%). There was a significant disparity in higher total hospital costs compared with government INA-CBGs costs (Rp. 9,238,022.09±1,265,801.88 vs 1,881,521.48±12,830.15; p<0.001). There was also an increase of LOS (p<0.001), total hospital cost (p<0.001), and cost disparity (p<0.01) in a higher severity level of vaginal delivery. Conclusion: Vaginal delivery costs in INA-CBGs scheme are underneath the actuarial value. There was also an increase in total hospital costs and a more significant disparity in the higher severity levels of vaginal delivery.